The Effect of The ELSIMIL Application on Adolescent Knowledge - Intan Gumilang Pratiwi; Baiq Yuni Fitri Hamidiyanti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
In West Nusa Tenggara Province, especially West Lombok Regency, the number and presentation of women according to the age of first marriage, a fairly high percentage occurs at the age of 16 - 19 years. The aim of thus study is to determine the effect of the ELSIMIL application on adolescent knowledge. This research uses a pre-experimental research method with a pre-post control group design. The sample in this study totaled 60 with details of 30 control groups and 30 intervention groups.In the intervention group and control group, a pre-test was carried out, then different interventions were given. The intervention group was given the ELSIMIL Application, the control group used the booklet. There is the influence of ELSIMIL the effect of the ELSIMIL application on adolescent knowledge. Recommendation for the next research It is hoped that future research will be able to use this approach mixed research better so that an assessment can be obtained deeper meaning.